Evaluation of Digital Educational Technologies by University Teachers - M.G. Sorokova; M. Odintsova; N.P. Radchikova (Moscow State University of Psychology and Education, 2023)
A comparative analysis of the assessments of digital educational technologies by teachers (mean age – 49±12 years) of various Russian Federation universities who have experience in using them in their professional activities (N=110) and teachers who do not have such experience (N=40) is carried out. The samples are equivalent in gender, academic titles and degrees, age, and work experience. The main advantages are the following: access to information at any convenient time; flexible schedule and the ability to organize independent work. Among the difficulties technical failures, lack of personal contacts, inconvenience of working with an electronic course and the need to spend a long time at the computer were noted. Teachers with experience in the development of e-learning courses rate work in an electronic environment much more positively, in contrast to teachers without experience who exaggerate the frequency of technical failures, point out the lack of technical and legal support, and the difficulties in monitoring assignments. All the teachers can be divided into “skeptics” and “enthusiasts” in relation to the acceptance of digital environment. “Enthusiasts”, unlike “skeptics”, have a positive attitude to innovations, believe that the educational process becomes more flexible and intense, emphasize the growth of student involvement and independence, individualization of training, support from management, colleagues, technical support, transparency of interaction. Most teachers with experience in using e-learning courses turned out to be “enthusiasts”. The groups of “enthusiasts” and “skeptics” do not differ in gender, age, and professional experience, which indicates the possible presence of “second order” barriers: pedagogical beliefs that prevent the acceptance of e-learning.